Acute vs cumulative benefits of metformin use in patients with type 2 diabetes and heart failure. Issue 11 (30th July 2018) - Weir, Daniala L.; Abrahamowicz, Michal; Beauchamp, Marie‐Eve; Eurich, Dean T.
Abstract : Aims: To evaluate the association between metformin use and heart failure (HF) exacerbation in people with type 2 diabetes (T2D) and pre‐existing HF using alternative exposure models. Materials and methods: We analysed data for patients with T2D and incident HF from a national US insurance claims database. We compared the results of several multivariable Cox models where time‐varying use of metformin was modelled as: (1) current use; (2) total duration of past use; and (3) use within the past 30 days or 10 days. The outcome was defined as time to HF‐related hospitalization. We then re‐analysed the data using flexible weighted cumulative exposure (WCE) models. Results: A total of 7620 patients with diabetes and incident HF were analysed. The mean (SD) patient age was 54 (8) years, and 58% ( n = 4440) were men. In all, 3799 individuals (50%) were exposed to metformin, and 837 HF hospitalizations (11%) occurred (mean follow‐up 1.7 years). Results of conventional models suggested potential acute benefits in reducing HF exacerbation with metformin use in the past 10 days (adjusted hazard ratio [aHR] 0.76, 95% confidence interval [CI] 0.60‐0.97), while WCE models, which provided a better fit for the data, suggested lack of a systematic effect (aHR 0.91, 95% CI 0.69‐1.20). Conclusions: Our results suggest that cumulative metformin exposure does not decrease the risk of HF‐related exacerbation. Use of other anti‐hyperglycaemic agents with proven efficacy in patients with HF should also be considered as treatment options in this population.